2020
DOI: 10.21203/rs.2.20842/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Non-elective hospital readmission or Death using a Composite Assessment of Cognitive and Physical Frailty in Elderly inpatients with Cardiovascular Disease

Abstract: Background: We aimed to assess the utility of the combination of the mini-mental state examination (MMSE) + clock drawing test (CDT) and the Fried phenotype for predicting non-elective hospital readmission or death within six months in elderly inpatients with cardiovascular disease (CVD).Methods: A single-center prospective cohort was conducted from September 2018 to February 2019. Inpatients ≥65 years old were recruited. Predictive validity was tested using a Cox proportional hazards regression model analysis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…29 Unfortunately, only a few studies with very limited number of patients have investigated the prognostic impact of cognitive frailty in patients with HF. 12,26,30 One of the strengths of our study is that we were able to demonstrate the prevalence and prognostic impact of cognitive frailty in a sufficient number of patients and events, which allows for a reliable analysis regarding the association between cognitive frailty and poor prognosis independent of other potential prognostic factors. Moreover, we demonstrated that the negative prognostic impact of cognitive frailty remained constant regardless of the tool used to define physical frailty.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…29 Unfortunately, only a few studies with very limited number of patients have investigated the prognostic impact of cognitive frailty in patients with HF. 12,26,30 One of the strengths of our study is that we were able to demonstrate the prevalence and prognostic impact of cognitive frailty in a sufficient number of patients and events, which allows for a reliable analysis regarding the association between cognitive frailty and poor prognosis independent of other potential prognostic factors. Moreover, we demonstrated that the negative prognostic impact of cognitive frailty remained constant regardless of the tool used to define physical frailty.…”
Section: Discussionmentioning
confidence: 97%
“…A sub-analysis of HF only among patients with coronary artery disease (n = 66) showed that 15.2% of patients had cognitive frailty. 26 A previous study investigating the impact of concurrent grip weakness and cognitive impairment on prognosis in elderly patients with HF (n = 56) found that 9% of patients had combined grip weakness and cognitive impairment. 28 Regarding the prognostic impact of cognitive frailty, the results of the aforementioned three-city study in France showed that cognitive frailty was associated with a 1.9-fold Adjusted for age; male gender; body mass index; estimated glomerular filtration rate; New York Heart Association III/IV; systolic blood pressure; left ventricular ejection fraction; history of atrial fibrillation, coronary artery disease, diabetes mellitus, chronic obstructive pulmonary disease, heart failure, and hypertension; smoking status; albumin, haemoglobin, sodium level, and log-transformed BNP at discharge; and prescription of angiotensin-converting enzyme inhibitor or angiotensin receptor blocker, beta-blocker, and mineralocorticoid receptor antagonist at discharge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations